Seagrass canopy structure mediates putative bacterial pathogen removal potential - Liu, Songlin; Wu, Yunchao; Luo, Hongxue; Ren, Yuzheng; Jiang, Zhijian; Zhang, Xia; Fang, Yang; Liang, Jiening; Huang, Xiaoping (Frontiers in Marine Science, 2023)
Bacterial pathogen removal function in seagrass meadows is gaining attention worldwide, with enhancing particle sedimentation as the main potential mechanism. Unfortunately, seagrass meadows are declining to patchiness and fragmentation due to anthropogenic activities and global climate change. However, effects of seagrass decline on the bacterial pathogen removal potential are poorly understood, limiting our ability to understand living coastal humans and marine organism suffered pressure of diseases and other health effects in response to seagrass decline. Here, we investigated the putative bacterial pathogens (including Vibrio spp., Salmonella spp., Staphylococcus spp. and Enterococcus spp.) abundances in the trapped particles under different canopy structure Enhalus acoroides patches in South China Sea. The Vibrio spp., Salmonella spp., and Staphylococcus spp. abundances of trapped particles were observed much greater under high density and height seagrass patches than other patches and significantly positive correlations with seagrass density and height were observed. This was mainly ascribed to high density and height seagrass patches can trap more particles. Surprisingly, however, the Enterococcus spp. abundances were shown negative correlations with density and area. Enterococcus spp. is generally inhibited in well-oxygenated environments, which the microenvironment of dissolved oxygen might be mediated by seagrass density and area. Overall, this research suggests that removal putative bacterial pathogens potential was inhibited in fragmented seagrass meadow, therefore living coastal humans and marine organisms might suffer increasing risk diseases due to the seagrass meadows decline.